PERAN TEORI QIRA’AT DALAM MEMAHAMI AYAT RELASI GENDER - Ahmad Muttaqin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Al-Quran at the first time was sent down to transform the bias gender relation. In relation to this, it is necessary to let the Quranic verses to talk about gender itself by using the variant readings (Qira’at) of the Al-Quran. This paper aims to built the argument how important the qira’at is to understand the verses talking about gender. For example, this will analyze the Q.S. Al-Nisa' (4):19. This concludes that wariant readings (qira’at) contributes to understand the Quran thematically and contextually. Second, using the qira’at in Q.S. Al-Nisa’ (4): 19, we understand how to position the women more respectfully.